Patient Mortality Is Associated With Staff Resources and Workload in the ICU. Issue 8 (August 2015) - Neuraz, Antoine; Guérin, Claude; Payet, Cécile; Polazzi, Stéphanie; Aubrun, Frédéric; Dailler, Frédéric; Lehot, Jean-Jacques; Piriou, Vincent; Neidecker, Jean; Rimmelé, Thomas; Schott, Anne-Marie; Duclos, Antoine
<x xml:space="preserve">Abstract</x> Objective: Matching healthcare staff resources to patient needs in the ICU is a key factor for quality of care. We aimed to assess the impact of the staffing-to-patient ratio and workload on ICU mortality. Design: We performed a multicenter longitudinal study using routinely collected hospital data. Setting: Information pertaining to every patient in eight ICUs from four university hospitals from January to December 2013 was analyzed. Patients: A total of 5, 718 inpatient stays were included. Interventions: None. Measurements and Main Results: We used a shift-by-shift varying measure of the patient-to-caregiver ratio in combination with workload to establish their relationships with ICU mortality over time, excluding patients with decision to forego life-sustaining therapy. Using a multilevel Poisson regression, we quantified ICU mortality-relative risk, adjusted for patient turnover, severity, and staffing levels. The risk of death was increased by 3.5 (95% CI, 1.3–9.1) when the patient-to-nurse ratio was greater than 2.5, and it was increased by 2.0 (95% CI, 1.3–3.2) when the patient-to-physician ratio exceeded 14. The highest ratios occurred more frequently during the weekend for nurse staffing and during the night for physicians (p < 0.001). High patient turnover (adjusted relative risk, 5.6 [2.0–15.0]) and the volume of life-sustaining procedures performed by staff (adjusted relative risk, 5.9 [4.3–7.9]) were also associated with increased mortality. Conclusions: This study proposes evidence-based thresholds for patient-to-caregiver ratios, above which patient safety may be endangered in the ICU. Real-time monitoring of staffing levels and workload is feasible for adjusting caregivers' resources to patients' needs.